2013
DOI: 10.1530/erc-13-0157
|View full text |Cite
|
Sign up to set email alerts
|

Assessing RET/PTC in thyroid nodule fine-needle aspirates: the FISH point of view

Abstract: RET/PTC rearrangement and BRAF V600E mutation are the two prevalent molecular alterations associated with papillary thyroid carcinoma (PTC), and their identification is increasingly being used as an adjunct to cytology in diagnosing PTC. However, there are caveats associated with the use of the molecular approach in fine-needle aspiration (FNA), particularly for RET/PTC, that should be taken into consideration. It has been claimed that a clonal or sporadic presence of this abnormality in follicular cells can d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…A wider use of immunocytochemical and genetic markers could prove useful in better defining the high-risk population. For example, patients with RET/PTC oncogene expression have a higher rate of lymph node metastases [49], and this could constitute a useful factor to consider in the future. The development of techniques for the intraoperative identification of metastatic lymph nodes could also help the surgeon in this difficult choice.…”
Section: Discussionmentioning
confidence: 99%
“…A wider use of immunocytochemical and genetic markers could prove useful in better defining the high-risk population. For example, patients with RET/PTC oncogene expression have a higher rate of lymph node metastases [49], and this could constitute a useful factor to consider in the future. The development of techniques for the intraoperative identification of metastatic lymph nodes could also help the surgeon in this difficult choice.…”
Section: Discussionmentioning
confidence: 99%
“…An arbitrary cut-off of 3% was employed, as control cells showed no split signal in 200 scored nuclei per sample. For the RET gene, a homebrew probe and a previously described cut-off value were used [19]. Microscopic analysis was performed with an Olympus BX41 epifluorescence microscope and a charge-coupled device camera (Cohu, San Diego, CA, USA) interfaced with the CytoVision system (software version 3.9; Applied Imaging, Pittsburg, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Most of those studies used a highly sensitive technique for analysis, which is capable of detecting a very small proportion of cells carrying a particular genetic event. Recently, a study demonstrated that fluorescence in situ hybridization (FISH) (Caria et al, 2013), the most sensitive method for detecting gene rearrangements in a single cell, could be used to distinguish nodules with abnormal follicular morpholoy with a ≥ 3% FISH signal for broken RET. When samples with a 6.8% break-apart FISH signal could be detected by RT-PCR and were proved to be malignant.…”
Section: Introductionmentioning
confidence: 99%